The effect of silencing immunity related genes on longevity in a naturally occurring Anopheles arabiensis mosquito population from southwest Ethiopia - Debalke, Serkadis (Parasit Vectors, 2019)
BACKGROUND: Vector control remains the most important tool to prevent malaria transmission. However, it is now severely constrained by the appearance of physiological and behavioral insecticide resistance. Therefore, the development of new vector control tools is warranted. Such tools could include immunization of blood hosts of vector mosquitoes with mosquito proteins involved in midgut homeostasis (anti-mosquito vaccines) or genetic engineering of mosquitoes that can drive population-wide knockout of genes producing such proteins to reduce mosquito lifespan and malaria transmission probability. METHODS: To achieve this, candidate genes related to midgut homeostasis regulation need to be assessed for their effect on mosquito survival. Here, different such candidate genes were silenced through dsRNA injection in the naturally occurring Anopheles arabiensis mosquitoes and the effect on mosquito survival was evaluated. RESULTS: Significantly higher mortality rates were observed in the mosquitoes silenced for FN3D1 (AARA003032), FN3D3 (AARA007751) and GPRGr9 (AARA003963) genes as compared to the control group injected with dsRNA against a non-related bacterial gene (LacZ). This observed difference in mortality rate between the candidate genes and the control disappeared when gene-silenced mosquitoes were treated with antibiotic mixtures, suggesting that gut microbiota play a key role in the observed reduction of mosquito survival. CONCLUSIONS: We demonstrated that interference with the expression of the FN3D1, FN3D3 or GPRGr9 genes causes a significant reduction of the longevity of An. arabiensis mosquito in the wild. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-019-3414-y) contains supplementary material, which is available to authorized users.